Capparaceae Juss. na restinga de Maricá, RJ - estudo sobre a biologia da reprodução de Capparis lineata Domb. ex Pers., C. flexuosa (L) L. e Cleome rosea Vahl. ex DC. - Lima, Heloisa Alves de (2002)
Studies floral biology, phenology and reproductive system of Capparis lineata Domb. ex Pers., Capparis flexuosa (L.) L. and Cleome rosea Vahl. ex DC., at sandy coastal plains ("restingas") of Maricá (RJ, Brasil), from 1997 to 2000. The two species of Capparis present white, dish-type, nectariferous, scented, hermaphrodite and nocturnal flowers. The pollination by sphingids had been confirmed based on observation of natural populations and by the finding of nocturnal lepidoptera's scales over the stigmas. Capparis lineata is a climber uncommon in the study area. It presents annual and synchronous flowering which remains from September (end of the cold and dry season) to December (rniddle of the hot and rainy season), with its peak in October. Capparis flexuosa varies from a prostrate shrub to a small tree and is found from the vicinity of the beach to the edge of the woods, being more common in the dense scrub communities at the sandy layers. It presents extensive flowering, during ten months in the year, with several episodes of floral emission, which are more synchronous in December, January and March (hot and rainy season), when the flowers last only one night, producing many fruits with many seeds. During the cold and dry season, the flowers remain attractive in the morning, and can be pollinated by Xylocopa ordinaria, generating, however, smaller fruits with fewer seeds. Considerations are risen about the participation of ants in the seed dispersion of C. flexuosa. The study shows a great morphological variability between the flowers of all the sphingophyllous species found at the study area, and also a strong seasonality of the flowering periods, tending towards the wet and hot season. Capparis lineata e C. jlexuosa are self-incompatible, with Fruit/Flower proportions of 6.9% and 45%, respectively. The possible causes of the low fruit-set of C. lineata has been investigated and evidences of pollinator limitation and selective abortion of fruits is presented. Cleome rosea is an annual monocarpic species. The natural and cultivated populations present female plants, with only pistilate flowers, and polliniferous plants, with hermaphrodite (7.9% to 48.7%), staminate (50% to 92.1%) and pistilate flowers (0 to 2.4%), characterizing a subdioecious sexual system. The zygomorphic, pink, nectariferous flowers of C. rosea are mainly pollinated by butterflies. The hennaphrodites flowers have intra-floral hercogamy, which prevent the spontaneous self-pollination, and, in general, are produced at the base of the inflorescences and precede the emission of the staminate flowers, characterizing an inter-floral dicogamy. Evidences are showed that the presence of developing fruits at the base of the inflorescences inhibit the new hemaphrodite flowers and accelerate the beginning of the staminate phase of flower emission. The species is self-compatible. The seeds produced by the female plants are always cross-fertilized, while the seeds produced by the polliniferous plants may be self-fertilized by geitonogamy. In natural conditions, the female plants produce more fruits and seeds, with smaller rate of abortion and greater rate of germination than the polliniferous ones.